1995
DOI: 10.1128/iai.63.7.2435-2442.1995
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipopolysaccharide (LPS), interleukin-1, interleukin-6, tumor necrosis factor, and dexamethasone in regulation of LPS-binding protein expression in normal hepatocytes and hepatocytes from LPS-treated rats

Abstract: Lipopolysaccharide (LPS)-binding protein (LBP) has been reported to be an acute-phase protein. LBP binds to LPS with a high affinity; LPS-LBP complexes then interact with the receptor CD14, resulting in increased expression of LPS-inducible genes. Hepatocytes represent a major source of LBP, but little is known about the regulation of rodent hepatocyte LBP synthesis. In these studies, undertaken to characterize hepatocyte LBP expression, we show that greater-than-20-fold increases in LBP mRNA levels in hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…These observations suggest that metabolic endotoxemia has a fluctuating nature in humans, and that fasting levels of LPS may therefore not be an accurate marker of chronic exposure to endotoxins over time. Some authors have also suggested the measurement of LBP, which is considered a longer-term marker of endotoxin-related exposure than LPS [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that metabolic endotoxemia has a fluctuating nature in humans, and that fasting levels of LPS may therefore not be an accurate marker of chronic exposure to endotoxins over time. Some authors have also suggested the measurement of LBP, which is considered a longer-term marker of endotoxin-related exposure than LPS [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Northern blot analysis was performed as previously described. 24 Twenty micrograms of each RNA sample was fractionated by electrophoresis through 1% agarose gel containing 3% paraformaldehyde. Equal loading was assessed by staining of agarose gels with ethidium bromide.…”
Section: Rna Extraction Reverse Transcription-polymerase Chain Reactmentioning
confidence: 99%
“…Total RNA was extracted with RNAzol as described previously [43]. For Northern blot analysis, total RNA (10 µg/well) was resolved by electrophoresis in 1% agarose gel containing 2.2 M formaldehyde before being transferred to Genescreen membrane (DuPont, NEN Research Products).…”
Section: Total Rna Isolation and Northern Blot Analysismentioning
confidence: 99%